Ask a New Question
Search
Prove: tan2x+sec2x = cosx+sinx/ cosx-sinx
prove that
(cosx - sinx) / (cosx + sinx) = sec2x - tan2x
2 answers
asked by
urgent
352 views
Prove:
tan2x+sec2x = cosx+sinx/ cosx-sinx
3 answers
asked by
Beatriz
4,864 views
PLEASEE HELPPMEEE!!!!
cot2x+sec2x=tan2x+csc2x and 1+2sinxcosx/sinx+cosx=sinx + cosx
1 answer
asked by
Sabrina
734 views
How would you solve the trigonometric identity (cosx-sinx)/(cosx+sinx)=sec2x-tan2x?
1 answer
asked by
Riley
464 views
Simplify #3:
[cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [cosx-(sin90cosx-cos90sinx)sinx]/[cosx-(cos180cosx+sinx180sinx)tanx] =
1 answer
asked by
Anonymous
1,054 views
I need to prove that the following is true. Thanks
(cosx / 1-sinx ) = ( 1+sinx / cosx ) I recall this question causing all kinds
0 answers
asked by
abdo
971 views
prove the identity
(sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= sinx^2 ^3 = (1-cosX^2)^3 = (1-2CosX^2 + cos^4) (1-cosX^2)
0 answers
asked by
JungJung
893 views
Prove the following functions:
(sinx+sin2x)/(1+cosx+cos2x)=tan x (cos3x/sinx)+(sin3x/cosx)=2cot2x tan2x=(2/cotx-tanx) theses are
2 answers
asked by
jared
1,075 views
Trigonometric Identities
Prove: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx +
0 answers
asked by
Dave
1,424 views
tanx+secx=2cosx
(sinx/cosx)+ (1/cosx)=2cosx (sinx+1)/cosx =2cosx multiplying both sides by cosx sinx + 1 =2cos^2x sinx+1 =
0 answers
asked by
shan
958 views